THE EFFECT OF INFLATION, INTEREST RATES AND EXCHANGE VALUE ON STOCK PRICES OF BANKING SECTOR COMPANIES ON THE INDONESIAN STOCK EXCHANGE - Deri Zulfitrah; Iqlima Azhar; Mayang Murni (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2022)
The research aims to determine: (1) The effect of inflation on share prices in banking sector companies listed on the Indonesian Stock Exchange in 2020-2022. (2) The effect of interest rates on share prices in banking sector companies listed on the Indonesian Stock Exchange in 2020-2022. (3) The influence of the exchange rate on share prices of banking sector companies listed on the Indonesian Stock Exchange in 2020-2022. (4) The influence of inflation, interest rates and exchange rates on banking sector companies listed on the Indonesian Stock Exchange in 2020-2022. Descriptive quantitative type, the sample for this research is banking sector companies listed on the Indonesian Stock Exchange in 2020-2022. The sample selection used a purposive sampling method, totaling 45 companies. The data analysis technique uses multiple regression analysis. The results of the analysis can be concluded that (1) Inflation has no significant effect on the share prices of banking sector companies listed on the Indonesian Stock Exchange in 2020-2022. (2) Interest rates have a significant influence on banking sector companies listed on the Indonesian Stock Exchange in 2020-2022. (3) The exchange rate does not have a significant effect on the share prices of banking sector companies listed on the Indonesian Stock Exchange in 2020-2022. (4) Inflation, interest rates and exchange rates do not have a significant effect on share prices in banking sector companies listed on the Indonesian Stock Exchange in 2020-2022.